Characterization of the Manufacturing Processes to Grow Triple-Junction Solar Cells - N. A. Kalyuzhnyy; V. V. Evstropov; V. M. Lantratov; S. A. Mintairov; M. A. Mintairov; A. S. Gudovskikh; A. Luque; V. M. Andreev (International Journal of Photoenergy)
A number of important but little-investigated problems connected with III-V/Ge heterostructure in the GaInP/GaInAs/Ge multijunction solar cells grown by MOVPE are considered in the paper. The opportunity for successfully applying the combination of reflectance and reflectance anisotropy spectroscopy in situ methods for investigating III-V structure growth on a Ge substrate has been demonstrated. Photovoltaic properties of the III-V/Ge narrow-band subcell of the triple-junction solar cells have been investigated. It has been shown that there are excess currents in the Ge photovoltaic p-n junctions, and they have the tunneling or thermotunneling character. The values of the diode parameters for these current flow mechanisms have been determined. The potential barrier at the III-V/Ge interface was determined and the origin of this barrier formation during MOVPE heterogrowth was suggested.